2016
DOI: 10.1002/2015ja021724
|View full text |Cite
|
Sign up to set email alerts
|

Survey of radiation belt energetic electron pitch angle distributions based on the Van Allen Probes MagEIS measurements

Abstract: A statistical survey of electron pitch angle distributions (PADs) is performed based on the pitch angle‐resolved flux observations from the Magnetic Electron Ion Spectrometer (MagEIS) instrument on board the Van Allen Probes during the period from 1 October 2012 to 1 May 2015. By fitting the measured PADs to a sinnα form, where α is the local pitch angle and n is the power law index, we investigate the dependence of PADs on electron kinetic energy, magnetic local time (MLT), the geomagnetic Kp index, and L she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…We assume an initial pitch angle distribution of f=f0false(E,Lfalse)sin3false(αfalse). The equatorially mirroring electron flux is calculated from the empirical electron model environment AE‐8 (Vette, ), f 0 ( E , L ), and the exponent is chosen considering Shi et al () who performed a survey on electron pitch angle distributions using Van Allen Probes MagEIS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…We assume an initial pitch angle distribution of f=f0false(E,Lfalse)sin3false(αfalse). The equatorially mirroring electron flux is calculated from the empirical electron model environment AE‐8 (Vette, ), f 0 ( E , L ), and the exponent is chosen considering Shi et al () who performed a survey on electron pitch angle distributions using Van Allen Probes MagEIS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Precomputed empirical models for electron pitch angle distribution can be useful for initial and boundary conditions, analytical estimates, etc. PSD models are legion in the literature (e.g., Vampola, ; Horne, Meredith, et al, ; Gannon et al, ; Xudong et al, ; Zhao et al, , ; Chen et al, ; Ni et al, ; Shi et al, ; Allison et al, , ). For instance, Denton et al (2015, Denton et al, ) derived an empirical model of particle fluxes in the energy range ~1 eV to ~40 keV at geosynchronous orbit based on a total of 82 satellite years of observations (between 1990 and 2007) made by LANL/GEO data.…”
Section: New Radiation Belt Modeling Capabilities and The Quantificatmentioning
confidence: 99%
“…They found that the occurrence rate of butterfly PADs is highest (~80%) at ~20–04 magnetic local time (MLT) at L > ~5.5, while ~50% occurrence rate of butterfly PADs is also observed at 11–15 MLT at L ~ 4, and the outer belt butterfly PADs do not show significant correlation with the solar wind dynamic pressure. Some studies have also focused on electron PADs in the slot region and inner belt (e.g., Lyons & Williams, , ; Shi et al, ; Zhao et al, , ). Lyons and Williams (, ), using 35‐ to 560‐keV electron data from Explorer 45, studied both quiet time and storm time structures of radiation belt electron PADs at 1.7 < L < 5.2.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that for ~460‐keV electrons, 90°‐minimum PADs are generally present in the inner belt and appear in the slot region during quiet times, normal PADs dominate at L ~ 3.5–4, and cap PADs generally appear in the slot region at the decay phase of storms and are likely caused by plasmaspheric hiss wave scattering. Shi et al (), using data from MagEIS instruments, performed a statistical survey of radiation belt electron PADs and their correlation with electron energy, MLT, geomagnetic Kp index, and L‐shell. They found that the electron PADs are more exceedingly peaked at 90° PA in the low L region, during active times, on the dayside, and for higher‐energy electrons.…”
Section: Introductionmentioning
confidence: 99%